Lysosomal acid lipase: at the crossroads of normal and atherogenic cholesterol metabolism - Dubland, Joshua A.; Francis, Gordon A. (Frontiers in Cell and Developmental Biology, 2015)
Unregulated cellular uptake of apolipoprotein B-containing lipoproteins in the arterial intima leads to the formation of foam cells in atherosclerosis. Lysosomal acid lipase (LAL) plays a crucial role in both lipoprotein lipid catabolism and excess lipid accumulation as it is the primary enzyme that hydrolyzes cholesteryl esters derived from both low density lipoprotein (LDL) and modified forms of LDL. Evidence suggests that as atherosclerosis progresses, accumulation of excess free cholesterol in lysosomes leads to impairment of LAL activity, resulting in accumulation of cholesteryl esters in the lysosome as well as the cytosol in foam cells. Impaired metabolism and release of cholesterol from lysosomes can lead to downstream defects in ATP-binding cassette transporter A1 regulation, needed to offload excess cholesterol from plaque foam cells. This review focuses on the role LAL plays in normal cholesterol metabolism and how the associated changes in its enzymatic activity may ultimately contribute to atherosclerosis progression.